PENGARUH SUMBER DAYA MANUSIA, MOTIVASI PERILAKU KERJA DAN KNOWLEDGE SHARING DALAM MENINGKATKAN KINERJA KADER PADA POSYANDU DI WILAYAH BUGU KIDUL PASURUAN - Sumartik Sumartik; Abdullah Hilmi Ar Rifani; Dewi Andriani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the influence of Human Resources, Work Behavior Motivation, and Knowledge Sharing on Cadre Performance at Posyandu in the Bugu Kidul Pasuruan area. This research uses a quantitative approach method by correlating human resources, work behavior motivation, knowledge sharing on performance which focuses on posyandu cadres in the Bugu Kidul Pasuruan area. In this research, the sampling technique used a total sampling technique. Total sampling is a method in which the entire research population is taken as a sample. The number of respondents in this study was 95 respondents which included the entire population that was the research subject. The data analysis approach for this research uses Partial Least Squares (PLS) which is based on Smart PLS version 4. Basically, PLS is a Structural Equation Modeling (SEM) approach that is more comprehensive than previous methods. The results of this research state that Human Resources, Work Behavior Motivation, Knowledge Sharing have a positive and significant effect on performance where T-values are 2,926 > T-table (1.96) with P-values of 0.002 < Sig level (< 0 .05). The researcher expresses his gratitude to readers who have followed and listened to this research. The researcher is also very open to constructive criticism and suggestions in order to improve the quality of scientific work in the future..